Reversing selectivity of bambusuril macrocycles toward inorganic anions by installing spacious substituents on their portals - Rando, Carola; Grewal, Surbhi; Sokolov, Jan; Kulhánek, Petr; Šindelář, Vladimír (Chemical science, 2025)
Two chiral bambusurils, which are diastereomers to each other, show remarkable differences in their binding affinity and selectivity toward inorganic anions as determined by isothermal titration calorimetry. These differences are explained by quantum-chemical calculations.